PENGARUH TERAPI KELOMPOK SUPORTIF TERHADAP KEMAMPUAN MENGATASI HALUSINASI PADA KLIEN SKIZOFRENIA DI RSUD TOMBULILATO - Nur Uyuun I. Biahimo; Fadli Syamsuddin; Susinta Ismail (Jurnal Anestesi, 2023)
Supportive Group Therapy is a therapy consisting of several people who plan, organize and respond directly to issues and pressures as well as adverse circumstances and is also a significant method of dealing with hallucination problems. Hallucinations experienced by individuals can be caused by precipitation and predisposing factors. The objective of research was to determine supportive group therapy on the ability to overcome hallucinations in schizophrenic clients at RSUD Tombulilato. Quasi-experimental research design with a group pretest – posttest one group design. Sampling used total sampling with 15 respondents. Data collection used an observation sheet with the results, there were 15 (100%) respondents controlling low hallucinations before being given supportive group therapy by 12 (80.0%) respondents and controlling high hallucinations by 3 (20.0%) respondents. After being given supportive group therapy, it controlled low hallucinations by 2 (13.3%) respondents and controlled high hallucinations by 13 (86.7%) respondents. Statistical test results used the paired t-test showed a p-value = 0.000 with ? <0.05, there was a significant influence between the effect of supportive group therapy on the ability to overcome hallucinations in clients with schizophrenia. It is expected the influence of supportive group therapy can improve the ability to deal with patient hallucinations.